Morphological and physical characteristics of nano-hydroxyappetite biocomposites for bone repair - Mohd Thani, Suryati (2017)
There was 3 phase in this study. The first phase was synthesized of nano-carbonated hydroxy appetite (nano-CHA) using the conventional microwave at 3 level of microwave power (300W, 600W, and 850W). It was found from TEM that all the synthesized powder was in targeted nano size, with insignificant differences in size (0.031-0.03 nm) among all the samples. For 300 W samples, the average size was 10.15±0.78 nm, while for 600 W and 850 W, were 10.19±0.86 nm and 10.18±0.97 nm, respectively. As for FTIR and XRD analysis, the samples exhibit the trend of hydroxyapatite peaks, regardless of level microwave power used. It is concluded that microwave power has no significant effect on nano-CHA produced. Hence, the power of microwave selected was 300 W in view of lower level of microwave power, therefore less electricity used. The second phase was the production of nano-CHA / gelatin scaffolds in three different ratios, 5:5 (50% nano-CHA/50% gelatin), 6:4 (60% nano-CHA/40 % gelatin) and 7:3 (70% nano-CHA/30% gelatin). The mechanical and physical properties of the bone scaffolds were analyzed. An ideal bone scaffold design was later chosen and proceed to in vitro study at the third phase. From TEM analysis, 5:5 nano-CHA/gelatin scaffold, the porosity of the scaffold were located mainly in the middle with pore size ranges from 97-639 μm. While for 6:4 the pores were equally scattered. For 7:3 scaffold, large horizontal crack across the scaffold was detected. Pore size for 6:4 and 7:3 ratio was 106-296 μm and 110-295 μm, respectively. As for porosity percentage, scaffold 5:5 have the highest porosity (67%) followed by 6:4 scaffold (60%) and lastly scaffold 7:3 (50%). Mechanical properties analysis of the scaffolds exhibit that, scaffold 6:4 have the highest yield strength (52.36 MPa) and modulus (853.73 MPa), followed by scaffold 5:5, 46.7 MPa and 684.23 MPa, respectively. Scaffold 7:3 has the lowest yield strength (28.46 MPa) and modulus (598.27 MPa). Next, for water absorption analysis, it can be seen that after 24 hours scaffold with 5:5 has the highest water absorption percentage (72%). While for degradation study, bone scaffold 5:5 and 6:4 showed a mild breakage, while sample 7:3 show a more rapid degradation manner, at week 6, all the bone scaffolds started to disintegrate at the same rate and complete loss of structure was recorded at week 12. Based on these outcomes, scaffold 6:4 (60% nano-CHA: 40% gelatin) was selected as an ideal bone scaffold. For DSC analysis, the onset temperature, T0was at 96.31 ̊C and the melting temperature, Tmof the ideal scaffold was detected at 331.34 ̊C, compatible with human body temperature. The FTIR trends, all the important functional groups of hydroxyapatite were presence. Next, EDX analysis found that carbon has the highest (w/w) %, 72.8% and calcium was detected with 2.58% (w/w) %. For in vitro study, the ideal scaffold shows a higher level of cells viability (0.14±0.03) compared to control culture medium (0.38±0.03), indicating good compatibility on cells viability. To further clarify, the fluorescence staining of acridine orange (AO) / propidium iodide (PI) signals was conducted. The results exhibit all of the cells were stained green representing the live cells with no sign of dead cells. Moreover, images from Environmental Scanning Electron Microscopy (ESEM) display perfect adhesion of the cell into scaffolds both inside and outside after 14 days of culture. Hence, it can be concluded that the ideal bone scaffold (6:4) is biocompatible to act as a bone replacer.